Toxicity analyses of surface water in selected industrial areas of Bogura sadar, Bangladesh (Research in Agriculture Livestock and Fisheries, 2019)
An investigation was carried out to assess the extent of ionic toxicity of surface water samples for agricultural usage in the Karatoya-Bangali Floodplain (2,577 sq. km). Fifteen water samples were collected from five industrial areas of Bogura sadar upazila to assess the dissolved chemical constituents and also to classify them on the basis of their comparative stability for agricultural usage. Water samples were collected from surface water sources viz., rivers, canals and ponds at Bogura sadar upazila. The chemical analyses included pH, electrical conductivity (EC), total dissolved solids (TDS), Ca, Mg, K, Na, Zn, Cu, Fe, Mn, Cd, Pb, B, As, CO3, HCO3, PO4, SO4 and Cl. The pH indicated that surface water samples were acidic to alkaline in nature (pH = 6.5-8.8). The electrical conductivity (EC) and sodium absorption ratio (SAR) revealed that all the surface samples were categorized as ‘medium salinity’ and ‘low alkalinity’ hazards with ‘excellent’ and ‘good’ in quality combining expressed as C2S1. Considering TDS all the surface waters were as ‘freshwater’. Soluble sodium percentage (SSP) indicated that all the surface water samples were ‘excellent’ and ‘good’ classes. Residual sodium carbonate (RSC) categorized the surface water samples as ‘suitable’ in quality for irrigation. The status of Ca, Mg, Na, K, Zn, Cu, As, B, Fe, CO3, SO4, PO4, and Cl were not hazards in the investigated area. In all surface water samples, HCO3 ion was considered as pollutant for irrigating crops. Rest ionic constituents were suitable for irrigation purposes. As, B, SO4, Cl and TDS were not problematic for drinking, TDS, Cd, Cu and Zn were not hazardous for livestock usage and SO4 and hardness (HT) were not problematic for aquaculture. But rest ionic constituents for these respective usages were toxic.Res. Agric., Livest. Fish.6(2): 227-234, August 2019